Feasibility of electromagnetically guided transjugular intrahepatic portosystemic shunt procedure. Issue 1 (2nd January 2017) - Isfort, Peter; Penzkofer, Tobias; Wilkmann, Christoph; Na, Hong-Sik; Kotzlowski, Christian; Ito, Nobutake; Pfeffer, Joachim Georg; Bisplinghoff, Stefan; Osterhues, Sabine; Besting, Andreas; Gooding, Jorge; Schmitz-Rode, Thomas; et al.
Abstract: Objectives: To develop an electromagnetic navigation technology for transjugular intrahepatic portosystemic shunt (TIPS) creation and translate it from phantom to an in-vivo large animal setting. Material and methods: A custom-designed device for TIPS creation consisting of a stylet within a 5 French catheter as well as a software prototype were developed that allow real-time tip tracking of both stylet and catheter using an electromagnetic tracking system. Feasibility of navigated TIPSS creation was tested in a phantom by two interventional radiologists (A/B) followed by in-vivo testing evaluation in eight domestic pigs. Procedure duration and number of attempts needed for puncture of the portal vein were recorded. Results: In the phantom setting, intervention time to gain access to the portal vein (PV) was 144 ± 67 s (A) and 122 ± 51 s (B), respectively. In the in-vivo trials, TIPS could be successfully completed in five out of eight animals. Mean time for the complete TIPS was 245 ± 205 minutes with a notable learning curve towards the last animal. Conclusions: TIPS creation with the use of electromagnetic tracking technology proved to be feasible in-vitro as well as in-vivo . The system may be useful to facilitate challenging TIPSS procedures.